(untitled) (Alternautas, 2022)
What alternatives to disaster recovery can we think of? What are the dynamics behind the ‘just recoveries’ of disasters? In ‘Island Futures’, Mimi Sheller invites us to envisage alternatives to development, disaster recovery and disaster capitalism in the Caribbean region. Thinking the Caribbean mainly from the Haitian experience, Sheller reflects on the workings of uneven post-disaster recovery in an era where the human-made ecological crisis has become more evident. In sum, she invites us to reflect on the implications of an “ever-worsening climate change driven by neoliberal capitalism” that will only produce more disasters and perpetuate underdevelopment if nothing is done to reverse the current trajectory.